2015
DOI: 10.1104/pp.15.00132
|View full text |Cite
|
Sign up to set email alerts
|

The Xanthomonas campestris Type III Effector XopJ Proteolytically Degrades Proteasome Subunit RPT6

Abstract: Many animal and plant pathogenic bacteria inject type III effector (T3E) proteins into their eukaryotic host cells to suppress immunity. The Yersinia outer protein J (YopJ) family of T3Es is a widely distributed family of effector proteins found in both animal and plant pathogens, and its members are highly diversified in virulence functions. Some members have been shown to possess acetyltransferase activity; however, whether this is a general feature of YopJ family T3Es is currently unknown. The T3E Xanthomon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 52 publications
0
44
0
Order By: Relevance
“…However, XopJ, a T3E from X. campestris pv vesicatoria 85-10, was shown to proteolytically degrade the 19S RP subunit RPT6 in order to inhibit proteasome activity and to interfere with SA-mediated defense in susceptible pepper host plants (Üstün et al, 2013;Üstün and Börnke, 2015). A similar mechanism has been proposed for the T3E HopZ4 from P. syringae pv lachrymans (Üstün et al, 2014).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, XopJ, a T3E from X. campestris pv vesicatoria 85-10, was shown to proteolytically degrade the 19S RP subunit RPT6 in order to inhibit proteasome activity and to interfere with SA-mediated defense in susceptible pepper host plants (Üstün et al, 2013;Üstün and Börnke, 2015). A similar mechanism has been proposed for the T3E HopZ4 from P. syringae pv lachrymans (Üstün et al, 2014).…”
Section: Discussionmentioning
confidence: 79%
“…The first bacterial T3Es identified that directly target the proteasome for defense suppression are XopJ from Xanthomonas campestris pv vesicatoria and HopZ4 from Pseudomonas syringae pv lachrymans. Both closely related T3Es interact with the proteasomal component RPT6, a subunit of the 19S RP, to inhibit proteasome activity (Üstün et al, 2013Üstün and Börnke, 2015). In effect, this results in impaired turnover of the SA master regulator NPR1 and the attenuation of SAdependent defense responses.…”
mentioning
confidence: 99%
“…Xanthomonas XopJ and HopZ4, a YopJ family protein from P. syringae , inhibit proteasome activity through interaction with the proteasomal subunit RPT6. The inhibitory effect is dependent on the plasma membrane localization and conserved catalytic triad of these effector proteins (Üstün and Börnke, ; Üstün et al ., ). Therefore, we investigated the effect of the N ‐myristoylation motif on various facets of AvrXccB function.…”
Section: Discussionmentioning
confidence: 99%
“…ACIP1 acetylation in planta alters its defence function (Cheong et al ., ). XopJ targets the host cell proteasome to suppress salicylic acid‐mediated plant defence (Üstün and Börnke, ; Üstün et al ., ). AvrXv4, like XopD, possesses a SUMO isopeptidase activity, and ectopic expression of AvrXv4 in plants results in a reduction in SUMO‐modified proteins (Roden et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…vesicatoria xopJ deletion mutant led to increased proteasome activity when compared with leaves infected with the wild-type strain (Üstün, Bartetzko and Börnke 2013). XopJ interacts with and degrades the ATPase RPT6 (regulatory particle ATPase 6) of the 19S regulatory particle of the 26S proteasome at the plant plasma membrane (Üstün, Bartetzko and Börnke 2013; Üstün and Börnke 2015) (Fig. 4F).…”
Section: Interference Of Type III Effectors With the 26s Proteasomementioning
confidence: 99%